Review of recent results on excursion set models - Wilson, Richard J. (Image analysis and stereology, 2001)
Many images consist of two or more "phases", where a phase is a collection of homogeneous zones. For example, the phases may represent the presence of different sulphides in an ore sample. Frequently, these phases exhibit very little structure, though all connected components of a given phase may be similar in some sense. As a consequence, random set models are commonly used to model such images. The Boolean model and models derived from the Boolean model are often chosen. An alternative approach to modelling such images is touse the excursion sets of random fields to model each phase. In this paper, the properties of excursion sets will be firstly discussed in terms of modelling binary images. Ways of extending these models to multi-phase images will then be explored. A desirable feature of any model is to be able to fit it to data reasonably well. Different methods for fitting random set models based on excursion sets will be presented and some of the difficulties with these methods will be discussed.
Keywords: Image Processing, Computer-Assisted; Modeli teoretski; Models, Theoretical; Slika, obdelava z računalnikom; Najmanjši-kvadrati, analiza; Normal Distribution; Normalna distribucija; Least-Squares Analysis; Likelihood Functions; Slučajnost, razporeditev; Random Allocation; Sulfidi; Verjetnostne funkcije; Sulfides; porazdelitev; modeli; verjetnost; analiza slik